2015
DOI: 10.1590/0104-07072015003030014
|View full text |Cite
|
Sign up to set email alerts
|

Fragments of Female Corporeality in Victims of Domesticviolence: A Phenomenological Approach

Abstract: This was a phenomenological study undertaken at the Women's Police Station in Guarapuava in the Brazilian state of Paraná that aimed to understand the significance of living with the offender after filing a domestic violence report at the station. Data were collected by means of interviews with 14 women victims of domestic violence, who continued to live with their attackers after reporting them. The women's discourses were interpreted through the lens of the framework of French philosopher Maurice MerleauPont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…In these cases, the body stores hurts that hurt beyond what it has suffered physically. 11 Research developed with women who experienced violence found similar characteristics as stress, anxiety and low self-esteem. 19 For these women, it is as if time does not pass and their lives be trapped in memories.…”
Section: Discussionmentioning
confidence: 98%
“…In these cases, the body stores hurts that hurt beyond what it has suffered physically. 11 Research developed with women who experienced violence found similar characteristics as stress, anxiety and low self-esteem. 19 For these women, it is as if time does not pass and their lives be trapped in memories.…”
Section: Discussionmentioning
confidence: 98%
“…8 Também é frequente o uso da violência psicológica como forma de intimidação para a violência sexual. 14 No nosso estudo, esse tipo de violência teve prevalência de aproximadamente 2,0%, semelhante ao encontrado em pesquisa realizada com 691 adolescentes de escolas públicas do Rio Grande do Sul, Brasil (2, 1%). 15 Ainda em relação à violên- Também foi identificada associação positiva entre as expressões físicas e sexuais com o alto risco para esses agravos, porém sem significância estatística.…”
Section: Discussionunclassified
“…Faced with maternal feelings of protection, as well as the need to provide a healthy family environment for the children, women feel the need to confront and break the cycle of violence. [23][24] Primary social networks are generated over time, and cannot be created or reproduced, because their configuration is strongly linked to the freedom of choice of individuals and even to the collectives that establish them. But they can be promoted, moved and oriented, in the way they are identified, recognized and valued.…”
Section: Discussionmentioning
confidence: 99%